Estudio de tiempos en la industria láctea en la ciudad de Latacunga - Bustillos Chicaiza, Dannes Humberto (2022)
The dairy industry "LATACUNGA" has as its main activity the elaboration of different dairy products such as: whole milk, semi-skimmed, skimmed, skimmed, lactose-free, fortified, sound, powdered milk, milk cream, yogurt, condensed milk and butter, this research study focuses on the production of whole milk because it is the most demanded product of the industry, The main problem that was identified is in the area of whole milk packaging, since the machinery suffers breakdowns during the production process which generates loss of time of the personnel involved in the process, the objective is to carry out a time study for the development of an improvement plan in the industry, The methodology used is an analytical study since the activities were carried out as the survey of the different processes of whole milk production and this allowed to represent all processes through flowcharts and analytical flowcharts for a better understanding, the procedure of the research project is the study of times once determined the production process and the areas of analysis, taking into account key factors such as the basic time, the valuation of the rhythm and the supplements to obtain the standard time that in turn determines the current capacity of the plant, at the end of this research project it is concluded that 19 minutes are optimized for each unit produced, which in units represents an increase of 2. 542 units per day and a 3% increase in productivity.